Association of Interleukin-32 with Progress of Coronary Artery Disease: A Case-Control Study - Rasha Mahdi Khalifa Al-Mamori; Abeer Thaher Naji Al-Hasnawi; Ali Jaleel Ali Al-Yassery (Karbala Journal of Medicine, 2025)
Background: Coronary artery disease (CAD) is a chronic inflammatory disease usually caused by atherosclerosis. Interleukin-32 (IL-32) is a recently identified inflammatory cytokine associated with an increased risk of cardiovascular diseases in inflammatory conditions. The aim of the study was to evaluate the role of IL-32 in patients with CAD and its relationship with their disease progression. Methods: The present study was a case-control study that included a control group of 50 healthy individuals and 50 CAD patients. Serum was drawn from all participants for the detection of IL32 serum level by the Enzyme-linked immunosorbent assay (ELISA) method. Results: Regarding the IL32 level, there were statistical differences (P =0.004) between the groups under study. In patients, compared to controls, there were increases in the IL-32 serum level. Additionally, patients with CAD showed a non-significant relationship regarding biomarkers, except erythrocyte sedimentation rate (ESR) and C-reactive protein (CRP) (p=0.002 and 0.000, respectively), which elevated in CAD patients compared to the healthy control group. Conclusions: The result of this study has shown an elevation in IL32 serum levels in patients with CAD compared to healthy individuals. Therefore, this interleukin may be related to the progression of the disease. Keywords: Coronary Artery Disease, IL32, ELISA